The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
OECD Guidelines on Measuring Subjective Well-Being 2013
DOI: 10.1787/9789264191655-8-en
|View full text |Cite
|
Sign up to set email alerts
|

Output and analysis of subjective well‑being measures

Abstract: This work is published on the responsibility of the Secretary-General of the OECD. The opinions expressed and arguments employed herein do not necessarily reflect the official views of the OECD or of the governments of its member countries or those of the European Union or those of the US National Research Council or the National Institute on Aging of the US National Institute of Health, which provided support for the work that led to this publication. This document and any map included herein are without prej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…While conceptually different to PWI and life satisfaction, happiness is closely related ( Medvedev & Landhuis, 2018 ) and an important construct to understand in relation to CSO global wellbeing. SWB score distributions in this study showed a typically-found skew, with most respondents reporting within the higher range ( OECD, 2013 ).…”
Section: Methodsmentioning
confidence: 56%
“…While conceptually different to PWI and life satisfaction, happiness is closely related ( Medvedev & Landhuis, 2018 ) and an important construct to understand in relation to CSO global wellbeing. SWB score distributions in this study showed a typically-found skew, with most respondents reporting within the higher range ( OECD, 2013 ).…”
Section: Methodsmentioning
confidence: 56%